Post-event visits as the sources of marketing strategy sustainability: a conceptual model approach - Li, Hui; Song, Wei; Collins, Roger (Journal of Business Economics and Management, 2014)
While extant literature has mainly concentrated on contemporaneous event tourism marketing (i.e., on visiting the city during or around the event) and on intentions to revisit after the event’s completion, this research investigates the impact of the event on the decisions of potential tourists/visitors who have never visited the host city and want to visit it after the event’s completion. Research in this area, especially in those emerging markets where event marketing is developing rapidly, is limited. In order to address the issues raised, a conceptual model is proposed. This model is based on a multivariate research approach, examining the interrelationships between event image, destination image, participants’ perceived satisfaction with the event and intentions to visit, under the context of non-repeat event marketing. Five hypotheses postulating these interrelationships were tested using structural equation modeling. A “non-repeat” event, the National Games, the biggest traditional sports event in China, was chosen to test this model. Selfadministered questionnaires were used to collect data relating to a period of two months after the event’s completion. The findings show that the sustainability of event marketing strategy can be achieved through the post-event visit to the host city. First published online: 15 Jan 2013